Wage-earning women : industrial work and family life in the United States, 1900-1930 - Tentler, Leslie Woodcock (Oxford University Press, 1982)
Writing with a keen eye for detail as well as a real empathy with the first generation of wage-earning women, Tentler reconstructs the day-to-day realities of life on the job, in the home, and in the industrial neighborhoods of major cities.